FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN UPAYA KESIAPSIAGAAN TANGGAP DARURAT KESELAMATAN DAN KESEHATAN KERJA (K3) DI LABORATORIUM KIMIA DEPARTEMEN X FAKULTAS Y UNIVERSITAS DIPONEGORO - Dewi Faridlotul Muafiroh; Suroto Suroto; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Prevention of emergencies could be made to prepairingpreparedness including some planning and preparations to prevent an emergency situation. Preparedness is one of important aspects which must exist in hazards area, such as working in laboratory.Laboratory should implement Occupational Safety and Health (OSH). In academic laboratory, the students gets deeply explanation about emergency situations from spilled chemical materials, or electrical damage that happen at any times. The Aim of this research is to analyze some factors related to Occupational Safety and Health (OSH) in chemical laboratory at X Departemen of Y faculty in Diponegoro University. The researchused analytical survey which Cross Sectional as the approching metod.the sample used on this research used on this study are 70 students. This research, there were observation paper about physical environment. The result on this research, showed that there were some variables that related in chemical laboratory at X Departement of Y Faculty in Diponegoro University, such as knowledge (p-value=0,042 α≤0,05) physical environment of emergency protection facilities (p-value=0,0004 α≤0,05). Meanwhile, there were some variables that did not relate to preparedness in chemical laboratory at X Departement of Y Faculty in Diponegoro University, such as gender (p value=0,926 α>0,05) attitudes (p-value=0,928 α>0,05), OSH monitoring (p-value=0,977 α>0,05), and standard operating procedure (p-value=0,818 α>0,05). On therefore, the X Departement is recommended to brief students before pratical sessions., make permanent procedures, do assessment of student’s competency in chemistry laboratory, add safety lesson and equipping the laboratory with emergency protection facility.